The Conservation of Chloroplast Genome Structure and Improved Resolution of Infrafamilial Relationships of Crassulaceae - Chang, Hong; Zhang, Lei; Xie, Huanhuan; Liu, Jianquan; Xi, Zhenxiang; Xu, Xiaoting (Frontiers in Plant Science, 2021)
Crassulaceae are the largest family in the angiosperm order Saxifragales. Species of this family are characterized by succulent leaves and a unique photosynthetic pathway known as Crassulacean acid metabolism (CAM). Although the inter- and intrageneric relationships have been extensively studied over the last few decades, the infrafamilial relationships of Crassulaceae remain partially obscured. Here, we report nine newly sequenced chloroplast genomes, which comprise several key lineages of Crassulaceae. Our comparative analyses and positive selection analyses of Crassulaceae species indicate that the overall gene organization and function of the chloroplast genome are highly conserved across the family. No positively selected gene was statistically supported in Crassulaceae lineage using likelihood ratio test (LRT) based on branch-site models. Among the three subfamilies of Crassulaceae, our phylogenetic analyses of chloroplast protein-coding genes support Crassuloideae as sister to Kalanchoideae plus Sempervivoideae. Furthermore, within Sempervivoideae, our analyses unambiguously resolved five clades that are successively sister lineages, i.e., Telephium clade, Sempervivum clade, Aeonium clade, Leucosedum clade, and Acre clade. Overall, this study enhances our understanding of the infrafamilial relationships and the conservation of chloroplast genomes within Crassulaceae.